Retail outlet choice and household buying behavior for fresh fruits and vegetables in Tagum City - Lastimado, Russell Mae P.
The retail industry in global scenario and even in the Philippines showed apparent changes especially in the retail food sector. Retail formats continue to expand, modernize, and changes, as well as the consumer pattern in purchasing fresh fruits and vegetables. In this study, three retail outlets were considered namely: Wet market, Supermarket and Others (mobilized vendors/neighborhood markets). The retail outlet choice and the buying behavior of the consumers in Tagum City were analyzed using the information obtained through household interviews. Based on the results, the consumers in wet market, supermarket and others have considered the same important retail attributes in purchasing fresh fruits and vegetables. They valued the price of products, convenience of location, food safety, cleanliness and product quality. However, in the econometric modeling, there were only retail outlets considered due to data variability: Wet Market and Others. The study used three major approaches namely ; Linear Probability Model and Probit Model. The best model was chosen for the two types of commodity group. Results suggest that Probit model was appropriate for fruits and vegetables. The Probit model for fruits identified household size, convenience of location and price of products as significant factors while for vegetables, it identified education, income, convenience of location, price of products, and product quality as the reasons affecting retail outlet choice.